2016
DOI: 10.3389/fpubh.2016.00204
|View full text |Cite
|
Sign up to set email alerts
|

Why We Move: Social Mobility Behaviors of Non-Disabled and Disabled Children across Childcare Contexts

Abstract: BackgroundSocial mobility is defined as the co-occurrence of self-directed locomotion and direct peer interaction. Social mobility is a product of dynamic child–environment interactions and thus likely to vary across contexts (e.g., classroom, gymnasium, and playground).PurposeThe purpose of this present study was to examine differences in children’s social mobility: (1) across contexts by age and (2) between non-disabled and disabled children.MethodParticipants (n = 55 non-disabled and three disabled children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…6). We believe her achievements in self-mobility not only benefited her physical well-being but also her development [27][28][29][30][31]. This link, between motor exploration and spatial aspects of development, point healthcare providers to a potential further advantage of enhancing a child's mobility by also enhancing cognition and development.…”
Section: Discussionmentioning
confidence: 79%
“…6). We believe her achievements in self-mobility not only benefited her physical well-being but also her development [27][28][29][30][31]. This link, between motor exploration and spatial aspects of development, point healthcare providers to a potential further advantage of enhancing a child's mobility by also enhancing cognition and development.…”
Section: Discussionmentioning
confidence: 79%
“…Despite the increasing number of studies on using PMDs for enhancing mobility and overall development, there is still limited evidence on the impacts of independent mobility and psychological development in young children with disabilities ( 14 , 27 , 54 ). To facilitate participation in play in different environments, Livingstone and Paleg’s Delphi study ( 17 ) suggested that the development of inexpensive, light weight, child- and family-friendly PMDs is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, independent mobility can instigate a cascade of developmental events in domains far afield from motor development. Indeed, disabilities that hamper locomotion impede opportunities for learning about things in the environment and limit social engagements with caregivers and peers [111] (Box 2).…”
Section: Suggestions For Developmental Researchmentioning
confidence: 99%